Design of active undamped and damped resonant absorber with guaranteed stability - Safiullah Timorian; Michael Valásek; Neusser Zdeněk; Nejat Olgac (Advances in Mechanical Engineering)
This paper deals with the development of a feedback control strategy on a SDoF (Single Degree of Freedom) absorber. It is desired to be resonant at two arbitrarily selected frequencies so that it suppresses vibration of primary system at these two frequencies. This problem has already been treated using time-delayed feedback control logic, which brings infinite dimensionality into the treatment. This paper offers a non-delayed feedback control logic with some additional benefits. It handles three facts of the problem: (a) the creation of a feedback logic to achieve resonance at two arbitrarily selected frequencies, (b) stability verification in real-time, (c) practical deployment of the control action. This method is applied to a single-mass primary structure. Two different tuning operations are considered: (i) for two precise and undamped resonances (ii) for two slightly-damped resonances. For both cases maps of stable operating frequencies are developed.